Factors Influencing Internal Medicine Resident Choice of Infectious Diseases or Other Specialties: A National Cross-sectional Study - Bonura, Erin M. (Clin Infect Dis, 2016)
Background. Only 49% of infectious diseases (ID) fellowship programs were filled in 2015 through the national match, but little is known about internal medicine (IM) resident perceptions of ID and factors related to IM resident career choice. Methods. We conducted 25 interviews and disseminated a Web-based survey to graduating IM residents in the United States utilizing a 2-stage sampling strategy. Participants were categorized into 3 groups based on interest in ID: (1) applied/intended to apply to ID; (2) interested in ID but did not apply; (3) never interested in ID. We conducted all analysis using poststratification adjustment weights with survey data analysis procedures. Results. Of the 590 participants, 42 (7%) selected category 1, 188 (32%) category 2, and 360 (61%) category 3. Most (65%) developed an interest in their ultimate career before residency. Of those interested in ID, >52% rated their ID medical school curriculum as very good and influential on their interest in ID. Ninety-one percent of category 2 participants felt mentorship was influential on career choice, although 43% identified an ID mentor. Category 2 chose salary as the most dissuading factor and the most likely intervention to increase ID interest. Conclusions. In this nationally representative sample of graduating IM residents, most develop an interest in their ultimate career before residency. Factors influencing this decision reside in both medical school and residency, which is consistent with career decision-making constructs. By identifying career determining factors and understanding how they fit into medical training frameworks, we can develop targeted initiatives to reinvigorate interest in ID.